STUDENTS’ PERCEPTION TOWARDS THE USE OF PICTURES AS A MEDIA TEACHING WRITING ON DESCRIPTIVE TEXT - habibi Nur Hidayanto (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2018)
STUDENTS’ PERCEPTION TOWARDS THE USE OF PICTURES IN WRITING DESCRIPTIVE TEXT  Habibi Nur HidayantoThe State Islamic Institute Of Surakartahbbnh10@gmail.com Abstract: The aims of this study are to find out whether the use of picture can improve the students’ writing skill on descriptive text and to find out the implementation of picture as a media in teaching writing on descriptive text. The study was carried out at the seventh grade of SMP Negeri 1 Gemolong Sragen. The sample of the research was the seventh grade of SMP Negeri 1 Gemolong Sragen. The samples were 40 students. The action research design was carried out collaboratively with senior English teachers in observing the implementation of picture as a media in teaching writing on descriptive text. This research consisted of three cycles. Every cycle consisted of three meetings. The results of the study showed that the use of picture as a media can improved the students' writing skills and the class condition became more enjoyable. Key words: students’ perception, media, picture, descriptive text, CAR